Examining a Youth-led Participatory Video Process in Disaster Risk Reduction Management in a Philippine Rurban Community - Mendoza, Trina Leah T.; Flor, Benjamina Paula G. (Silliman Journal, 2025)
This paper explores what constitutes a youth-led participatory video (PV) process in disaster risk reduction management (DRRM) in a flood-prone community in Bay, Laguna, Philippines. It also aims to discuss the youth’s concepts of DRRM and PV. A PV training workshop was conducted from January to March 2019, along with qualitative interviews, focus group discussions, and participant observation. Youth’s concepts of DRRM primarily centered on disaster preparedness through information dissemination and capacity building. They appreciated the PV process because they were able to learn new knowledge and skills in PV production and DRRM and produce an advocacy video on typhoon preparedness. The generated grounded theory is that a youth-led PV process is a learning and capacity-building process that enables adults and youth to realize the latter’s capacity and shared responsibility to participate in DRRM initiatives. It serves as an entry point and strategy in community organizing. Through a PV process, participants build their capacities, co-construct knowledge, develop critical awareness, and take action to improve their situation. Beyond empowerment, PV is a development communication tool that helps participants realize their capabilities to become partners in development and live meaningful lives.